Knowledge sharing and sustainable competitive advantage: Mediating role of innovation culture and MSMEs business performance - Meyna Cinta Ratulian; Sabihaini Sabihaini; Fauzilah Salleh; Januar Eko Prasetio (Asian Management and Business Review)
This research aims to investigate how business performance (BP) and innovation culture (IC) mediate the relationship between knowledge sharing (KS) and sustainable competitive advantage (SCA) of MSMEs operating in Yogyakarta, Indonesia. The survey method was employed to gather the necessary data for this research. The population and sample consisted of 50 MSMEs. The unit of analysis in this study is the MSMEs fashionpreneur Jogja Fashion Dunia Incubation Program, which is represented by the owner and manager, who also serves as the respondent. The analysis method employed in this research is Partial Least Squares (PLS) using SmatPLS 4 software. The investigation results demonstrate that knowledge sharing has a significant impact on both the innovation culture and long-term competitive advantage. Additionally, the study reveals that the innovation culture significantly influences business performance and lasting competitive advantage. However, it is worth noting that business performance does not have a noticeable effect on sustainable competitive advantage. Furthermore, the study indicates that the relationship between knowledge sharing and sustainable competitive advantage is mediated by the innovation culture. On the other hand, when business performance acts as a mediator, the effect of the innovation culture and knowledge sharing on competitive advantage is indiscernible. To create exceptional customer value, policymakers and MSME management must showcase a firm dedication to innovation and connect it to supply chain agility, also known as SCA. Ultimately, this will result in comprehensive and enduring business performance.